2023
DOI: 10.33395/owner.v7i2.1296
|View full text |Cite
|
Sign up to set email alerts
|

Pengujian Fraud Triangle Theory Dalam Menjelaskan Kecurangan Laporan Keuangan Menggunakan Beneish M-Score

Abstract: Financial statements must be reliable and free from bias as they represent management accountability to investors. Yet, companies have many incentives to manipulate financial statements to meet investors’ performance expectations. Therefore, this study aims to examine the fraud triangle theory (pressure proxy by financial stability, opportunity proxy by nature of the industry, and rationalization proxy by total accrual to total assets) in explaining factors that cause management to commit fraud on financial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This gives a signal that when committing fraud, management uses the accrual principle, which shows the rationalization carried out by management, which is carried out by recognizing profits based on the principle of recognizing unearned income. The results of this study are in line with the results of research from Yesiariani & Rahayu (2017), Irwandi et al, 2020;Kuang & Natalia (2023), Narsa et al (2023), which found an influence between justification and fraudulent financial statements.…”
Section: C) Effect Of Justification On Fraudulent Financial Statementssupporting
confidence: 92%
See 2 more Smart Citations
“…This gives a signal that when committing fraud, management uses the accrual principle, which shows the rationalization carried out by management, which is carried out by recognizing profits based on the principle of recognizing unearned income. The results of this study are in line with the results of research from Yesiariani & Rahayu (2017), Irwandi et al, 2020;Kuang & Natalia (2023), Narsa et al (2023), which found an influence between justification and fraudulent financial statements.…”
Section: C) Effect Of Justification On Fraudulent Financial Statementssupporting
confidence: 92%
“…The results of this research conducted by (Kuang & Natalia, 2023)stated that there is a positive influence between justification and fraudulent financial statements. This gives a signal that when committing fraud, management uses the accrual principle, which shows the rationalization carried out by management, which is carried out by recognizing profits based on the principle of recognizing unearned income.…”
Section: C) Effect Of Justification On Fraudulent Financial Statementsmentioning
confidence: 77%
See 1 more Smart Citation